KRAS, p53 and BRAF Gene Mutations and Aneuploidy in Sporadic Colorectal Cancer Progression - Daniele Calistri; Claudia Rengucci; Ian Seymour; Elena Leonardi; Mauro Truini; Davide Malacarne; Patrizio Castagnola; Walter Giaretti (Cellular Oncology)
Background: The origin and mechanisms of chromosomal instability are still widely unknown. We previously investigated a limited number of human sporadic colorectal cancers (CRCs) and observed a statistically different occurrence of KRAS and p53 mutations among predetermined subgroups of tumors with different degrees of DNA aneuploidy. The aim of the present study was to further verify these observations by including BRAF gene analysis and by investigating a larger series of cases subdivided into Dukes' stages A to D to reconstruct some form of chronological modulation for events during CRC progression. Methods: KRAS, p53, BRAF mutations and flow cytometric DNA Index were evaluated by established techniques in a series of 135 human sporadic CRCs. Results: p53, KRAS and BRAF mutations were found in 39%, 34%, and 4% of tumors, respectively. The frequency of p53 mutations increased from 15% for stage A to 48% for stage D and was highest in near-diploid (DI 1.6) tumors. A similar correlation between gene mutations and DI values was observed for KRAS. The simultaneous presence of KRAS and p53 mutations was observed in only 11% of cases. Moreover, the co-occurrence of p53 and KRAS mutations was only observed in near-diploid and high-aneuploid tumors. Conclusion: Our findings suggest that KRAS and p53 gene mutations, which are rarely simultaneous and are associated with specific DI aneuploid values, do not represent a synergistic evolutionary pathway but may influence mechanisms of chromosomal instability.